Contextual Dynamics of Professional Identity Development in ELT Indonesian Graduate Students: A Grounded Theory Method - Urbaq , Sintia Marlina (Jurnal Pedagogy, 2024)
Through the ever-changing nature of globalized English Language Teaching (ELT) enterprises, graduate students are urged to engage in ELT to continuously construct, develop, and improve individual professional identity (PI) which is very essential. This process is crucial for students to be recognized as competent teachers and as respected professional in ELT community, creating opportunities for achieving individual future career aspirations.  Therefore, this research aimed to explore the impact of cultural environment and personal experience in the development of ELT professional, examining the interplay between self-identified PI, individual identity development strategies, and personal cultural education among ELT graduates. The research applied grounded theory method and used interviews as the major instrument to gather data from four ELT Indonesian graduate students with diverse backgrounds and experiences. The outcome of this finding showed that ELT graduates had firmly defined individual PI as intermediate-level professional, skills teachers, and multi-students of experts in the field of ELT. Moreover, partakers crafted and refined this identity by following self-identification and expanded personal insights through additional teaching or programs such as refining teaching skills, research capabilities, and active engagement in community service. Diverse professional backgrounds of ELT graduates impacted individual level of PI development. During this research, two participants showed a high level, while others signified a moderate, and a low level of PI. Those with a high level were teachers in formal and informal settings.